2020
DOI: 10.1007/s00421-020-04335-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional regional bi-ventricular shape remodeling is associated with exercise capacity in endurance athletes

Abstract: Aims: Endurance athletes develop cardiac remodeling to cope with increased cardiac output during exercise. This remodeling is both anatomical and functional and shows large interindividual variability. In this study, we quantify local geometric ventricular remodeling related to long-standing endurance training and assess its relationship with cardiovascular performance during exercise. Methods:We extracted 3D models of the biventricular shape from end-diastolic cine Magnetic Resonance images acquired from a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
7
0
6
Order By: Relevance
“…Whereas on the left side of the heart, an increased volume output can be established without much change in LV pressure, the pulmonary circulation is too short to provide volume buffering, resulting in important changes in RV pressure during exercise. 31 Indeed, the observed RV basal and septal shape remodeling in adults born SGA shares some similarities with those found in sportsinduced remodeling, 10,31 although the population born SGA in our study did not exercise more (often on the contrary) than their control counterparts. The observed remodeling may indicate that the RV of adults born SGA would be regularly subjected to higher pressures, suggesting that the pressure increase with moderate exercise would be larger in these adults compared with adults born at normal weight.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Whereas on the left side of the heart, an increased volume output can be established without much change in LV pressure, the pulmonary circulation is too short to provide volume buffering, resulting in important changes in RV pressure during exercise. 31 Indeed, the observed RV basal and septal shape remodeling in adults born SGA shares some similarities with those found in sportsinduced remodeling, 10,31 although the population born SGA in our study did not exercise more (often on the contrary) than their control counterparts. The observed remodeling may indicate that the RV of adults born SGA would be regularly subjected to higher pressures, suggesting that the pressure increase with moderate exercise would be larger in these adults compared with adults born at normal weight.…”
Section: Discussionsupporting
confidence: 61%
“…19 Ventricular shape differences between those born SGA and controls were assessed by SSA. 7,10,20 Statistical shape analysis was used to compute a reference shape for each population (controls and SGA) separately to compare them. Next, the specific remodeling in each individual (biventricular remodeling score) was estimated.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the RV outlet, it was previously demonstrated that this region could be exposed to high wall stress during exercise [25] and that the occurrence of ventricular tachycardia of outflow tract origin could be part of the physiological remodeling process in athletes [26]. Nevertheless, the RV outlet enlargement was inconstantly associated with exercise training [8,24,27,28]. Even when using 3D echocardiography-derived cross-sectional planes, the endocardial border tracings to outline the RV outflow tract and the pulmonary valve position remain challenging, as shown by our reproducibility analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The volume load of endurance exercise is a stimulus to the excentric hypertrophy seen in sports with a high dynamic component [ 26 , 27 ]. Previous categorization of sports in terms of their propensity to induce cardiac remodelling has been questioned and newer studies put more emphasis on the individual training intensity and duration, expressed as fitness that can be objectively measured in a maximal cardiopulmonary exercise test allowing the quantification of maximal oxygen consumption, VO 2 max [ 28 ]. Earlier studies have shown a close correlation between the level of fitness and cardiac chamber sizes as well as LVM [ 29 ] which we also found in this study, further supported by findings in linear LV-dimensions.…”
Section: Discussionmentioning
confidence: 99%